Hubungan Pola Makan dan Aktivitas Fisik Dengan Kejadian Stroke di Wilayah Kerja Puskesmas Sekupang di Kota Batam 2020 - Justiyulfah Syah; Savitri Gemini; Made Tantra Wirakesuma; Hanafi Hanafi; Siti Ramadania (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Diet and physical activity are the causes of stroke. The incidence of stroke in Batam in 2018 was 11.2%. A poor diet and consuming less fiber are more at risk of stroke, In addition to diet, lack of physical activity also tends to trigger degenerative stroke. This study aims to determine the relationship between diet and physical activity with the incidence of stroke. This type of research is analytic with a cross-sectional design. A sample of 67 respondents aged ≥ 45 years who were in the working area of the Sekupang Community Health Center with purposive sampling technique and data analysis used the Chi-Square test. Based on the results of the study, there was no significant relationship between diet and the incidence of stroke with a dietary p-value of 1.00 (α> 0.05) and there was a significant relationship between physical activity and stroke incidence of 0.003 (α <0.05). ), to the patient or the patient's family to increase the consumption of foods with various types of food, the right frequency of eating and the amount of food to meet energy, and to be diligent in doing physical activities such as sports to reduce the incidence of stroke.